The Utilization of Local’s Beji Soybean For Improving The Welfare of The Community - Sumarmi, Sulastri Isminingsih, Budi Setiadi Daryono Diah Rachmawati & Ari Indrianto (PROCEEDING ICBS, 2011)
Soybean is an important food crop. Productivity of local soybean needs to beimproved to support community food security. Research in the framework of Education forsustainable development has implemented since April until September 2011 in the village ofBeji, District Ngawen, Gunung Kidul Regency, Yogyakarta Special Region. Counseling andtraining of soybean processing was done to educate the public. Soybeans seed areprocessed into 'soybean milk' and added to the manufacture of ‘tiwul’ to enhance protein inthese traditional foods. Communities are trained to process tempe and tofu into nuggets tocreate a variety of flavors. After the training they are expected to increase nutritional intake,especially for the Beji village children and rural communities become healthier.Keywords: soybean, welfare, community